Stimulating effects of submerged plants on removing of N from the water in the Daihai lake of inner Mongolia autonomous region, China - Yao, Yipeng; Jiang, Yuhan; Liu, Yuhong; Meng, Shuang; Hu, Bintao; Chen, Yixue (Frontiers in Environmental Science, 2023)
The Daihai Lake, the third largest lake in Inner Mongolia Autonomous Region, is the cornerstone to maintain the ecosystem balance in this region, which is facing some problems including size shrinking, water quality declining and biodiversity decreasing largely in recent years. In order to quantify the N purification amount of submerged plants, Stella software was used in this study to construct a nitrogen dynamic model to simulate the nitrogen cycle process in the Daihai Lake and the participation of submerged plants in this cycle process. The results showed that based on the submerged plant growth area in 2019 in the Daihai Lake, the N uptake by submerged plants this year was 5.13t, accounting for 4.8% of all exogenous pollution (107.895t), Moreover, our model also predicted that the purification capacity of the restored submerged plants with a large area of 9.91 km2 in the Daihai Lake was significantly higher than before restoration. And the N pollution load of 107.892t in the Daihai Lake could be purified by this stored pattern in 12 years, while during this process a regular cleaning of submerged plant residues was required. Therefore, only large area restoration of submerged plant would benefit for improving water quality.